2006
DOI: 10.1158/1078-0432.ccr-05-1970
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct p53 Protein Isoform Signature Reflects the Onset of Induction Chemotherapy for Acute Myeloid Leukemia

Abstract: Purpose: The antioncogene protein product p53 has not been studied previously in cancer patients during in vivo chemotherapy.This study examined the early p53 protein and gene expression during induction chemotherapy in acute myeloid leukemia (AML). Experimental Design: Leukemic cells were collected from five AML patients during their first 18 hours of induction chemotherapy and examined for p53 protein and gene expression by one-and two-dimensional gel immunoblot and high-density gene expression arrays. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 49 publications
3
90
0
4
Order By: Relevance
“…We did not examine in detail p53 transcriptional activity in primary AML blast cells here; however, studies by our group have shown that expression of p53 target genes, including p21 and Bax, can be detected in AML blasts during in vivo therapy. 30 Typically, the p53 response of malignant cells is disabled by loss of heterozygosity of p53 or by loss of p53 pathway effectors. 6,31 The finding that wild-type p53 in AML blast cells was phosphorylated following DNA damage caused by a common chemotherapeutic agent is particularly striking (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine in detail p53 transcriptional activity in primary AML blast cells here; however, studies by our group have shown that expression of p53 target genes, including p21 and Bax, can be detected in AML blasts during in vivo therapy. 30 Typically, the p53 response of malignant cells is disabled by loss of heterozygosity of p53 or by loss of p53 pathway effectors. 6,31 The finding that wild-type p53 in AML blast cells was phosphorylated following DNA damage caused by a common chemotherapeutic agent is particularly striking (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…15 Features were extracted using Agilent Microarray ScannerBundle v7.5.1 and were processed using J-Express Pro v2.7 (www.molmine.com) to filter and normalize data from each hybridization and compile gene expression profile matrix data sets. 15 Analysis was restricted to patients with normal cytogenetics and FLT3-ITDs, and Significance Analysis of Microarrays (SAM) in J-Express Pro 2.7 was used to examine the correlation of gene expression data between AML cells with (10 patients) and without (nine patients) NPM1 mutations. SAM used 400 permutations of the sample sets to estimate the false discovery rate.…”
Section: Microarray and Real-time Quantitative Pcr Analysismentioning
confidence: 99%
“…Real-time quantitative PCR was performed as previously described. 15 Dilution series of pooled samples were used for the generation of standard curves for each TaqMan assay including the endogenous control, glyceraldehyde-3-phosphate dehydrogenase. Samples were tested in duplicates.…”
Section: Microarray and Real-time Quantitative Pcr Analysismentioning
confidence: 99%
“…The human p53 gene can encode at least nine different p53 protein isoforms: p53, p53ß, p53Á, Δ133p53, Δ133p53ß and Δ133p53Á are produced by alternative splicing of the intron 9, and alternative usage of the alternative promoter in intron 4, and Δ40p53 (p47), Δ40p53ß and Δ40p53Á -produced by alternative splicing of intron 9, and alternative intitiation of translation or alternative splicing of intron 2 (14). p53 isoforms have been described in breast cancer, acute myeloid leukemia, neuroblastoma, and in squamous cell carcinoma of the head and neck (17)(18)(19)(20)(21). In leukemia the appearance of a low molecular weight form of p53 is inversely correlated with the response to induction chemotherapy (17).…”
Section: Introductionmentioning
confidence: 99%
“…p53 isoforms have been described in breast cancer, acute myeloid leukemia, neuroblastoma, and in squamous cell carcinoma of the head and neck (17)(18)(19)(20)(21). In leukemia the appearance of a low molecular weight form of p53 is inversely correlated with the response to induction chemotherapy (17). Despite all the experimental evidence showing the importance of p53 in preventing carcinogenesis, it is difficult in clinical studies to link p53 status to cancer treatment and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%